Training for integrality in Health Care Careers: Potential for an Interprofessional Project - Rossit, Rosana; Batista, Sylvia Helena; Alves Batista, Nildo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
This study highlights the importance of interprofessional education in health for the learning process of the teamwork and integrality in care to expand effectiveness of services and quality of care. Former students from undergraduate health courses in Federal University of São Paulo/UNIFESP, Brazil (physical education, physical therapy, nursing and occupational therapy) responded to the questionnaire RIPLS to assess attitudes and readiness to three factors: teamwork and collaboration, professional identity and patient-centered care. The results showed this essential for health professionals development of competencies: problem solving, decision making, leadership, trust and respect to each other, communication with patients and other professionals, understanding the nature of the problems, understanding the clinical cases from the patient´s point of view. Eighty -four percent of the former students of the undergraduate courses were satisfied with the training received and provided contributions to the analysis of health education in the perspective of interprofessional education.